Auger Spectra and Different Ionic Charges Following 3s, 3p and 3d Sub-Shells Photoionization of Kr Atoms - Lotfy, Y.A; El-Shemi, A.M. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The decay of inner-shell vacancy in an atom through radiative and non-radiative transitions leads to final charged ions. The de-excitation decay of 3s, 3p and 3d vacancies in Kr atoms are calculated using Monte-Carlo simulation method. The vacancy cascade pathway resulted from the de-excitation decay of deep core hole in 3s subshell in Kr atoms is discussed. The generation of spectator vacancies during the vacancy cascade development gives rise to Auger satellite spectra. The last transitions of the de-excitation decay of 3s, 3p and 3d holes lead to specific charged ions. Dirac-Fock-Slater wave functions are adapted to calculate radiative and non-radiative transition probabilities. The intensity of Kr⁴⁺ ions are high for 3s hole state, whereas Kr³⁺ and Kr²⁺ ions have highest intensities for 3p and 3d hole states, respectively. The present results of ion charge state distributions agree well with the experimental data. Remove selected